Building a self-balancing scooter II - Chin, Cheng How (2014)
This report covers comprehensive review of the project on basic working principle of self-balancing vehicle, shortcomings of previous prototype, specs and features of new prototype, assembly details and programming code procedure. The aim of the project is to understand the working mechanism of self-balancing vehicle and develop a better prototype in the perspective of safety, low cost, aesthetic pleasing and manufacture-friendly. The self-balancing scooter is a vehicle which has 2 coaxial wheels driven independently by a controller that balances the vehicle with or without a rider. It was designed and built based on the principles of the inverted pendulum system and functions similarly to that of the Segway Personal Transporter. The vehicle recognizes the direction of gravity in which it constantly tries to stay under, through the signals provided by the accelerometer and the gyroscope. These signals are then interpreted by the microcontroller into commands to drive the motors in order to achieve balancing. In this report, much coverage is given to the improvement of mechanical structure includes more powerful motor and battery, more robust chassis and new safety features. Details about mounting and assembly of each part were described clearly to provide better understanding of the scooter structure. Furthermore, the report also covers the concept and development of the steering system and control system which equipped the reader with better understanding on the self-balancing mechanism of inverted pendulum. Changes and future improvements to the mechanical, electrical and software components of the scooter have been discussed to improve not only functionality and performance, but also the ease of use and safety of the scooter. Test has been conducted in different types of terrain such as small ramps, tight corners and gentle slopes. The results prove that the vehicle is able to operate well in the context of personal transporter. Overall, this project was successfully completed with a self-balancing scooter that is easy and enjoyable to ride on, yet providing an enriching experience and a very good learning platform as a final year project.